Toward Revision of the 'Best Practice for Diabetic Patients on Hemodialysis 2012' - Masanori Abe; Tomomi Matsuoka; Shunsuke Kawamoto; Kota Miyasato; Hiroki Kobayashi (MDPI AG, 2022)
Diabetic nephropathy is the leading cause of dialysis therapy worldwide. The number of diabetes patients on dialysis in clinical settings has been increasing in Japan. In 2013, the Japanese Society for Dialysis Therapy (JSDT) published the "Best Practice for Diabetic Patients on Hemodialysis 2012". While glycated hemoglobin (HbA1c) is used mainly as a glycemic control index for dialysis patients overseas, Japan is the first country in the world to use glycated albumin (GA) for assessment. According to a survey conducted by the JSDT in 2018, the number of facilities measuring only HbA1c has decreased compared with 2013, while the number of facilities measuring GA or both has significantly increased. Ten years have passed since the publication of the first edition of the guidelines, and several clinical studies regarding the GA value and mortality of dialysis patients have been reported. In addition, novel antidiabetic agents have appeared, and continuous glucose monitoring of dialysis patients has been adopted. On the other hand, Japanese dialysis patients are rapidly aging, and the proportion of patients with malnutrition is increasing. Therefore, there is great variation among diabetes patients on dialysis with respect to their backgrounds and characteristics. This review covers the indices and targets of glycemic control, the treatment of hyperglycemia, and diet recommendations for dialysis patients with diabetes.